Antigen-presenting cell-derived signals determine expression levels of CD70 on primed T cells. - Lens, S M (1997)
Interaction between CD27 and its ligand CD70 provides a second signal for T-cell proliferation and tumour necrosis factor-alpha (TNF-alpha) production. Whereas CD27 is broadly expressed during T-cell development, expression of CD70 in vivo is restricted. To determine when CD27 CD70 interactions can occur in immune reactions, we here analysed the regulation of CD70 expression on activated T cells. Mitogenic stimulation of purified T cells with either immobilized CD3 monoclonal antibody (mAb) or a combination of CD2 mAb induces only low levels of CD70 membrane expression. Markedly expression of the CD27-ligand is strongly enhanced by antigen-presenting cells (APC) and APC-associated signals such as interleukin-1 alpha (IL-1 alpha). IL-12, TNF-alpha and CD28-ligation. In contrast, T-cell derived cytokines, such as IL-4, counteract CD70 up-regulation on activated T cells. Analysis of the small subset of circulating CD70+ T cells revealed that these cells have a primed phenotype as they express CD45RO and HLA-DR antigens and are in high frequency able to secrete interferon-gamma (IFN-gamma). We conclude that T-T interactions involving CD27 and CD70 are likely to occur relatively early in immune reactions, after productive T-cell priming by APC and that expression of CD70 on circulating T cells is a reflection of recent priming by antigen.